THE EFFECTIVENESS OF USING YOUTUBE VIDEO IN TEACHING ENGLISH GRAMMAR VIEWED FROM STUDENTS’ ATTITUDE - Kurniawati, Dewi (Universitas Islam Negeri Raden Intan Lampung, 2013)
The research aims at investigating the effect of using YouTube video inteaching English grammar. The research was conducted at the English EducationProgram in Lampung in 2012. The population was all of the first semesterstudents of English Education Program. The sample of the study consisted of 72students distributed randomly on one experimental class who was taught by usingYouTube video and one class as control class who was taught by using textbooks.The instruments for collecting the data were a questionnaire on students’ attitudeto find out the students who have positive and and negative attitude, and agrammar test to find out the students’ achievement in learning grammar.Analysing data using ANOVA or analysis of variance and Tukey test leads to theconclusion that: (1) YouTube video as media ( = 27.75) is more effective thantextbooks ( =24.41) to teach grammar; (2) the students who have positive attitudehave higher achievement ( =29.11) than those who have negative attitude( =23.05); and (3) there is an interaction between teaching media and students’attitude.